IMPLEMENTATION OF INTEGRATED ETHNOSCIENCE INTERACTIVE E-MODULES IN ENERGY MATERIALS IN LIFE SYSTEMS ON LEARNING OUTCOMES OF CLASS VII STUDENTS - Hayandi, Atiqah Ulya; Diliarosta, Skunda (Department of Science Education, 2024)
The 21st century, revolution industry 4.0, and the 2013 curriculum require students to be able to take advantage of information and communication technology and require students to be more active in learning, as well as student-centered learning. However, in reality the students have not been active in learning and the learning time for energy material in living systems has not been effective. One solution to this problem is to implement an integrated science interactive e-module integrated with ethnoscience so that students can learn actively and independently. The purpose of this study was to determine the effect of an integrated science interactive e-module integrated with ethnoscience on energy material in living systems that is significant for class VII student learning outcomes. This type of research is a quasi-experimental design with a non-equivalent control group design. The experimental class used an integrated science interactive e-module integrated with ethnoscience, while the control class used printed teaching materials. The results of the data analysis show that there is an effect of the implementation of an integrated Ethnoscience integrated science interactive e-module on energy material in living systems that is significant for class VII student learning outcomes.